Investigation of the thermoelectric response in conducting polymers doped by solid-state diffusion. (March 2019) - Kang, K.; Schott, S.; Venkateshvaran, D.; Broch, K.; Schweicher, G.; Harkin, D.; Jellett, C.; Nielsen, C.B.; McCulloch, I.; Sirringhaus, H.
Abstract: Thermoelectric effect is a physical phenomenon which intricately relates the thermal energy of charge carriers to their charge transport. Understanding the mechanism of this interaction in different systems lies at the heart of inventing novel materials which can revolutionize thermoelectric power generation technology. Despite the recent surge of interest in organic thermoelectric materials, the community has had difficulties in formulating the charge transport mechanism in the presence of a significant degree of disorder. Here, we analyze the thermoelectric properties of various conducting polymers doped by solid-state diffusion of dopant molecules based on a transport model with a power law energy dependence of transport function. A fine control of the degree of doping via postdoping annealing provides an accurate empirical evidence of a strong energy dependence of the carrier mobility in the conducting polymers. A superior thermoelectric power factor of conducting polymers doped by solid-state diffusion to that of other doping methods can be attributed to a resulting higher intrinsic mobility and higher free carrier concentration. Graphical abstract: The thermoelectric response of highly conducting polymers including poly(2, 5-bis(3-tetradecylthiophen-2-yl)thieno[3, 2-b]thiophene) doped by solid-state diffusion of tetrafluoro-tetracyanoquinodimethane is investigated over a wide range of doping levels by a controllable de-doping. The Seebeck coefficient-conductivity relationship reveals the underpinning strong energy dependence of charge transport and sheds light upon crucial transport parameters that enhance the thermoelectric power factor in conducting polymers.Image 1